2002
DOI: 10.2214/ajr.178.2.1780419
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of MR Imaging in the Diagnosis of Peripheral Tears of the Triangular Fibrocartilage of the Wrist

Abstract: MR imaging does not adequately reveal the peripheral attachment of the triangular fibrocartilage complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
1
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(75 citation statements)
references
References 17 publications
0
69
1
5
Order By: Relevance
“…Multiple factors can play a major role in MRI accuracy in detecting TFCC lesions; the magnetic field strength is one of these factors as it was shown by Anderson et al who suggested that imaging with 3.0 T offers higher quality at a given spatial resolution [10]. Special coils were used while scanning and the area under investigation also have their reflection on the accuracy of imaging [15,20]. Moreover, Haims et al reported that MRI was not accurate in detecting TFCC abnormalities, especially peripheral tears (avascular area), and that the experience of the radiologist interpreting the MRI findings has a significant influence on the ability to detect and localize TFCC abnormalities [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple factors can play a major role in MRI accuracy in detecting TFCC lesions; the magnetic field strength is one of these factors as it was shown by Anderson et al who suggested that imaging with 3.0 T offers higher quality at a given spatial resolution [10]. Special coils were used while scanning and the area under investigation also have their reflection on the accuracy of imaging [15,20]. Moreover, Haims et al reported that MRI was not accurate in detecting TFCC abnormalities, especially peripheral tears (avascular area), and that the experience of the radiologist interpreting the MRI findings has a significant influence on the ability to detect and localize TFCC abnormalities [20].…”
Section: Discussionmentioning
confidence: 99%
“…Special coils were used while scanning and the area under investigation also have their reflection on the accuracy of imaging [15,20]. Moreover, Haims et al reported that MRI was not accurate in detecting TFCC abnormalities, especially peripheral tears (avascular area), and that the experience of the radiologist interpreting the MRI findings has a significant influence on the ability to detect and localize TFCC abnormalities [20].…”
Section: Discussionmentioning
confidence: 99%
“…Their conclusion was that MRI without intra-articular contrast medium is unreliable in excluding tears of the intrinsic ligaments. Moreover, despite showing a high accuracy of 97% for central and radial sided TFC tears [30,35,50,59] (Palmer's class IA, ID and class II tears), MRI is only 64% accurate [15,50] for peripheral tears of the ulnar attachment (Palmer's class IB and IC). The poor performance of MR for these tears was attributed to the presence of high-signal vascularized fibrous tissue between the two ulnar attachments, the ligamentum subcruentum [3,15], which can mimic a tear.…”
Section: Discussionmentioning
confidence: 99%
“…Haims et al found that the sensitivity, specificity and accuracy of detection of peripheral ulnar tear were only 17%, 79% and 64% only (31).…”
Section: Pitfalls Of Mri In Tfcc Tear Detectionmentioning
confidence: 99%
“…This peripheral tear is the most commonly missed. Indirect clues include altered morphology, excessive fluid accumulation and focal synovitis around this region (31). MR arthrography of the DRUJ will also help to depict tears at the foveal attachment.…”
Section: Mri Features Of Tfcc Tearmentioning
confidence: 99%